The Association of Maternal Sleep Quality with Newborn Health - Rahmi Andrita Yuda; Amel Yanis; Hudila Rifa Karmia (Institute of Computer Science (IOCS), 2022)
Sleep disturbances in pregnancy according to the literature, they can affect newborn outcomes also can impact the growth and development of the baby.This study evaluated the effect of maternal sleep quality with newborn health. The research design was a cross-sectional study.The sample of this study were mothers who gave birth by cesarean delivery method with gestational age ≥ 37 weeks without complications, totally 78 pregnant women. The maternal sleep quality were assessed by PSQI questionnaire. Newborn Health (neonatal birth weight, body length and APGAR SCORE) were assessed by neonatal medical record. BDNF levels checked using the ELISA. Data were analyzed by Independent T-test and Mann-Whitney Test. There was no significant association between Maternal Sleep Quality with neonatal birth weight (p= 0,177).There were significant association between Maternal sleep quality with body length and APGAR SCORE of neonates with p value <0.05 (p = 0.025)(p=0,002). There was also a significant relationship between maternal sleep quality and neonatal cord blood BDNF levels (p=0.00). Sleep disturbances can impact obstetric conditions and newborn health. In this study there was no significant relationship between maternal sleep quality with neonatal birth weight.